The Difficult Dialogues of Reforming Issues in Yemen’s Drama, A Case Study of TV Series Hami Hamak, And Foursa Akhirah - BaMukaideh, Mohammed Anas (Journal of Humanities & Social Sciences, 2019)
This study aimed to identify the reality of Yemeni TV drama, through the drama’s lens as an art form of reform issues via a difficult dialogue perspective, in order to monitor the hubs of difficult dialogues through reforming issues, qualitative approach of case study through the analytical observation of a total of eighty-seven episodes were used, the study has reached a number of results, most important of which were: the occupation of political reform issues had a prominent position in the dramatic presentation among the native drama production compared to other reforming issues such as economic or social reform issues, at the other hand self-empowerment of the other were the main expression between the dramatic characters axis of the main dialogues in both cases, while diversity has been noted in addressing verity of reform issues despite the genera differences, the major dialogues were reflected in the form of "What Happened?" in both cases. The study has concluded that; the Yemeni TV drama has reflected a multiple reforming issues in Yemen’s society, especially the political reform issues, by presenting difficult dialogues in a similar environment to the reality despite the differs of a reformist issues importance. the researcher has envisioned the future of Yemeni drama to remain presence locally before it gets the importunity to cross geographical boundaries at a significant level due to many factors, perhaps the most important one is the diversity of local dialects in Yemen.